The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3989/gya.0227151
|View full text |Cite
|
Sign up to set email alerts
|

Advanced olive selections with enhanced quality for minor constituents

Abstract: SUMMARY:Squalene, phytosterols and tocopherols are minor constituents of paramount importance for the olive fruit and oil quality. The objective of this research was to conduct a two-year evaluation of these compounds in the fruits of seven advanced breeding selections. They were mainly selected for early bearing and high oil content from progenies of crosses between the cultivars 'Arbequina' and 'Picual'. An analysis of variance showed high genotypic effects, non-significant year effects, and genotype x year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Similar conclusions were reached by Beltrán et al [12] for cultivars ‘Picual’, ‘Hojiblanca’, and ‘Frantoio’, but not with what was collected in a previously published review by Uceda et al [32], which reported a low level of influence of the crop year. Significant effect of genotype and crop year was also found in other study including breeding selections from the same parentage than this work [33].…”
Section: Resultssupporting
confidence: 80%
“…Similar conclusions were reached by Beltrán et al [12] for cultivars ‘Picual’, ‘Hojiblanca’, and ‘Frantoio’, but not with what was collected in a previously published review by Uceda et al [32], which reported a low level of influence of the crop year. Significant effect of genotype and crop year was also found in other study including breeding selections from the same parentage than this work [33].…”
Section: Resultssupporting
confidence: 80%
“…The presence and the evolution of the α-tocopherols were genetically related while significant differences were observable between the two studied years. Annual biochemical changes and differences in annual rainfall and temperature are known to be responsible for the different conditions of each year that accelerate or delay ripening by increasing or decreasing the content of vitamins such as tocopherols [35,36]. [26] documented that their level is influenced by the harvest method and the storage temperature and time.…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant difference in total tocopherol content for different RI values and for different harvest years (p = 0.2465). Velasco et al (2015) found that the total tocopherol normal range in VOO is 100-250%; for the Arbequina variety from the Cabra region in Spain, the authors reported a concentration of 148% as the median RI. Values found in this study were higher than those for both harvest years and for all studied RI values.…”
Section: Tocopherolsmentioning
confidence: 96%